Long‐term overall‐ and progression‐free survival after pentostatin, cyclophosphamide and rituximab therapy for indolent non‐Hodgkin lymphoma. (28th February 2019) - Khashab, Tamer; Hagemeister, Fredrick; Romaguera, Jorge E.; Fanale, Michelle A.; Pro, Barbara; McLaughlin, Peter; Rodriguez, M. Alma; Neelapu, Sattva S.; Fayad, Luis; Younes, Anas; Feng, Lei; Vega, Francisco; et al.
Summary: In a prospective phase II trial, pentostatin combined with cyclophosphamide and rituximab (PCR) induced strong responses and was well‐tolerated in previously untreated patients with advanced‐stage, indolent non‐Hodgkin lymphoma (iNHL). After a median patient follow‐up of more than 108 months, we performed an intent‐to‐treat analysis of our 83 participants. Progression‐free survival (PFS) rates at 108 months for follicular lymphoma (FL), marginal zone lymphoma (MZL) and small lymphocytic lymphoma (SLL) were 71%, 67% and 15%, respectively, and were affected by clinicopathological characteristics. Ten‐year PFS rates for those with beta‐2‐microglobulin levels <2·2 and ≥2·2 mg/l prior to treatment were 71% and 21%, respectively. Patients without bone marrow involvement had 10‐year PFS rates of 72% vs. 29% for those with involvement. At time of analysis, the median overall survival (OS) had not been reached. The OS rate was 64% at 10 years and differed significantly based on histology: 94% for FL, 66% for MZL and 39% for SLL. Long‐term toxicities included 18 (21·7%) patients with second malignancies and 2 (2·4%) who developed myelodysplastic syndrome after receiving additional lines of chemotherapy. Our 10‐year follow‐up analysis confirms that PCR is an effective, robust and tolerable treatment regimen for patients with iNHL.